Efektivitas Mobile Health dan Supportive Education untuk Meningkatkan Kepatuhan Manajemen Perawatan Diri Pasien Hipertensi (Journal of Telenursing (JOTING), 2023)
This study aims to evaluate the effectiveness of mobile health interventions and supportive education in increasing self-care management compliance in hypertensive patients. The research method used is a literature review through databases, namely Scopus, Science Direct, Web of Science and Sage Journal. The results of 10 research articles report that interventions using mobile technology (m-health) and supportive educational interventions are very effective in increasing medication adherence in hypertensive patients. Conclusion, Interventions using mobile technology (m-health), combined with supportive educational interventions can be applied to increase self-care management compliance in hypertensive patients. Keywords: Supportive Education, Hypertension, Compliance, Mobile Health